1998
DOI: 10.1021/jp981326l
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Dependent Adhesion between Opposed Perfluoropoly(alkyl ether) Layers:  Dependence on Chain-End Functionality and Chain Length

Abstract: Adhesion was measured repeatedly between opposed molecularly thin layers of perfluoropoly(alkyl ether)s on mica, with particular attention to the dependence of the adhesion on chain-end functionality and chain length of the polymer. The polymer layers were kept in contact for specified times that differed by 4 orders of magnitude (0.01-500 s) and then unloaded (separated) at rates that varied by 5 orders of magnitude (0.003-120 µm/s of a detachment device with spring constant 1.1 × 10 4 N/m) using a modified s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…4). This is consistent with previous results on molecularly thin PFPE films from the literature [19][20][21].…”
Section: Discussionsupporting
confidence: 94%
“…4). This is consistent with previous results on molecularly thin PFPE films from the literature [19][20][21].…”
Section: Discussionsupporting
confidence: 94%
“…The presence of molecules bridging the two surfaces has been suggested in a study of rate-dependent adhesion, where DOL showed a slightly stronger increase in adhesion force with separation rate than was observed for monofunctionalized samples. It is possible that such bridging would contribute to the adhesion observed in Figure .…”
Section: Discussionmentioning
confidence: 94%
“…The van der Waals attraction ( F/R = − A /6 D 2 , where the Hamaker constant calculated according to van der Waals−Lifshitz theory 55 is A = 2.47 × 10 -20 J for mica interacting across Fomblin-Z with ε = 2.03 and n = 1.294 70 ) is very small at the separations where adhesion was observed in these systems and cannot account for the values measured. In a previous study on rate-dependent adhesion it has been suggested that possible bridging of difunctionalized chains (hydroxyl-terminated Fomblin-Z) from one surface to the other might occur. We will return to the adhesion results after discussing possible structure of the film.…”
Section: Discussionmentioning
confidence: 99%
“…Granick et al 10,11 have also studied the tribology of confined Zdol and Z03 with the SFA. These authors find values of D 0 that are substantially larger, by a factor of 2 in some FIG.…”
Section: A Film Thickness Under Loadmentioning
confidence: 99%